2011
DOI: 10.1002/pssc.201001043
|View full text |Cite
|
Sign up to set email alerts
|

Properties of surface‐pit related emission in a ‐plane InGaN/GaN quantum wells grown on r ‐plane sapphire

Abstract: We have investigated the optical and structural properties of non‐polar (11‐20) In0.03Ga0.97N/GaN multiple quantum wells (MQWs) grown on r‐plane sapphire substrates. The emission spectrum is characterised by a peak at ∼370 nm and a blue‐green emission band (400–550 nm). The near‐UV peak at 370 nm is assigned to carrier recombination in the MQWs lying on the (11‐20) plane. On the basis of microscopy and cathodoluminescence imaging, the longer wavelength band is attributed to emission from sidewall MQWs formed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, when the growth orientation deviated from the c-axis [0001], structural defects increased [4], and attaining smooth surface became difficult. Large surface pit is one of themorphological imperfections that frequently encountered in a-plane(1120) GaN growth [5][6][7].It refers to the inverted triangular pyramid pits that bound by one vertical (0001 � ) and two inclined{101 � 1}facets [8]or,in some studies, pentagonal shapes composed of{101 � 2 � }, {202 � 1}, and {112 � 2} facets [9,10]. Reducing the V/III ratio could eliminate these defects; therefore, most researchers considered them as a result of incomplete island coalescence [5,6,[8][9][10][11][12], which was due to the increased vertical growth of the (1120) facet and decreased lateral growth rate of the inclined facets, such as {101 � 1} and (0001 � ) [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the growth orientation deviated from the c-axis [0001], structural defects increased [4], and attaining smooth surface became difficult. Large surface pit is one of themorphological imperfections that frequently encountered in a-plane(1120) GaN growth [5][6][7].It refers to the inverted triangular pyramid pits that bound by one vertical (0001 � ) and two inclined{101 � 1}facets [8]or,in some studies, pentagonal shapes composed of{101 � 2 � }, {202 � 1}, and {112 � 2} facets [9,10]. Reducing the V/III ratio could eliminate these defects; therefore, most researchers considered them as a result of incomplete island coalescence [5,6,[8][9][10][11][12], which was due to the increased vertical growth of the (1120) facet and decreased lateral growth rate of the inclined facets, such as {101 � 1} and (0001 � ) [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Their structural properties will be reported in more detail elsewhere. 15) Cross-sectional transmission electron microscopy (TEM) studies of the samples show that, as found in the hexahedron-shaped V- defects of high-indium content c-plane InGaN QWs, 16) a TD is associated with each surface-pit. Furthermore, the surfacepit density, determined via AFM, is proportional to the density of partial dislocations, determined from plan-view TEM measurements of the underlying GaN templates.…”
mentioning
confidence: 95%